Development of Teacher Digital Literature Competence Improvement Model Based on School MGMP to Enhance E-Learning (Educational Management, 2021)
This study aims to determine the MGMP-based teacher digital literacy competency development model's effectiveness in improving E-Learning. The research design used is Research and Development (R&D), which is a 4-D (four_D) development model, namely defining, designing, developing, and disseminating. The subjects were 40 vocational teachers (12 Accounting, 10 Office, 8 Automotive and 10 Marketing teachers). The teachers followed the process of coaching model activities. Data collection techniques used interviews, tests, questionnaires, and documentation, the types of data used were qualitative and quantitative. Quantitative research results were obtained from the results of the development stage and limited trials. The assessment of the model's validity by experts got a score of 51.75 in the excellent category. The model's effectiveness is evidenced by the achievement of the competency skills of teachers in managing e-learning, obtaining a score of 3.75 in the very good category, while the results of cognitive competence, the understanding concept of digital literacy competence developed are effective in improving e-learning. This is evidenced by the average value of the final test, which is 84.75, which is greater than the average value of the initial test, which is 71.27.